Transcatheter closure of ventricular septal defects: early and midterm results - Samar Hassan Mohamed Ahmed Nasser; Mohamed Samir; Rasha Amar; Sahar Shaker (Cairo : Samar Hassan Mohamed Ahmed Nasser, 2021)
Background: Ventricular septal defect (VSD) is a common form of congenital heart disease and can occur in isolation or in combination with other structural defects. They represent nearly 20% of all congenital heart lesions and are encountered in different positions within the ventricular septum. Aim To report early and mid-term results of percutaneous closure in all types of VSD in our cardiac unit Patients and methods We conducted a retrospective study with a total of 85 cases underwent transcatheter repair for VSD. We included patients from Pediatric Cardiology Clinic in Cairo University Specialized Children Hospital in the period between 2010 and January 2020 . We evaluated patients regarding; their baseline characteristics, VSD description, devices used, and complication developed whether during device inserting or later during the follow up. Patients were followed up to seven years.Results In the current study we included 85 patients , Majority of our patients had PM VSD (72.9%) with size ranging between 4 to 8 mm (78.8%). Most of VSD were closed by Amplatzer device (89.4%). During procedure ; 4.7% of cases had failed implantation , 1.2% of cases had Heart Block , 4.7% of cases had residual shunt and 11.8% of cases had vascular insufficiency .Conclusion Transcatheter closure of VSD with is safe and effective procedure. With the newly developed devices, there is a significant decrease in the risk for redo surgery and procedure related complications
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Complications; Transcatheter device closure; VSD